PENGARUH GAYA HIDUP REMAJA TERHADAP PENGGUNAAN KOSMETIK CREAM TEMULAWAK DI NAGARI PITALAH KECAMATAN BATIPUH - Dara Masela; Merita Yanita (Universitas Negeri Padang, 2022)
This study aims is to investigate the lifestyle of teenagers, the use of ginger cosmetics, and the effect of teenage lifestyle using ginger cosmetics cream in Nagari Pitalah, Batipuh. The population of this study are 50 girls in Nagari Pitalah. The sample in this study 30 people using random sampling technique. The research instrument used a Likert scale questionnaire with 52 items of statements. Data analysis used SPSS version 20.00 program. The study of the resu1ts can be conc1uded that 1) the youth lifestyle in Nagari Pitalah, Batipuh District with a respondent's achievement level of 67.9% is in the sufficient category, 2) the use of whitening cream for ginger in Nagari Pitalah, Batipuh District with a respondent's achievement level of 67.8% is in the sufficient category 3) there is a lifestyle influence on the use of ginger whitening cream because tcount> t table (9.272> 2.042) with a contribution of 75.4%. Suggestions in this study are 1) For researchers, to research more deeply about the lifestyle that can affect the use of ginger whitening cream, 2) For adolescents, this research is in order to increase adolescent knowledge about the use of ginger whitening cream, 3) For majors, research This is so that it can be used as an additional reference for the Libraries in the Makeup Study Program and the Faculty of Tourism, Padang State University which researches the lifestyle and use of whitening creams.